Students’ Professional Self-Education Ability as a Base for Developing the Subjective Position in Training Process - N. A. Rosina (Образование и наука)
The paper considers the students-psychologists’ readiness for the sub- jective educational activity, the peculiarities of the subjective position of the activities in question being described. The author regards the professional self-educational abil- ity as the key element of educational subjectivity. The essence and structure of the discussed phenomenon along with its main components – motivational, intellectual, regu- lating and reflexive – are revealed by means of interdisciplinary theoretical analysis and systematic theoretical and applied modeling.The schemes of the structural organization of the professional self-educational ability for the students-psychologists are given to provide the psychological guidelines for developing the upgrading educational programs corresponding with the require- ments of the Higher School Reorganization.